2020
DOI: 10.1038/s41598-020-68461-w
|View full text |Cite
|
Sign up to set email alerts
|

Infrared photodetector sensitized by InAs quantum dots embedded near an Al0.3Ga0.7As/GaAs heterointerface

Abstract: Mid-infrared sensors detect infrared radiation emitted from objects, and are actually widely used for monitoring gases and moisture as well as for imaging objects at or above room temperature. Infrared photodetectors offer fast detection, but many devices cannot provide high responsivity at room temperature. Here we demonstrate infrared sensing with high responsivity at room temperature. The central part of our device is an Al 0.3 Ga 0.7 As/GaAs heterostructure containing inAs quantum-dot (QD) layer with a 10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Next, we would note that zero-dimensional nanostructures have also been playing an important role in developing innovative sensing technologies. One of the examples in this direction includes longwave-infrared remote sensing and spectral imaging devices, in particular the development of quantum-dot infrared photodetectors [ 58 , 59 ]. As in the number of cases already considered by us, it should be emphasized that the knowledge of bandstructure here is critical too, because, e.g., the bias-dependent spectral response of these devices is brought about by the asymmetric bandstructure of the dot-in-a-well configuration.…”
Section: Low-dimensional Nanostructures and Sensorsmentioning
confidence: 99%
“…Next, we would note that zero-dimensional nanostructures have also been playing an important role in developing innovative sensing technologies. One of the examples in this direction includes longwave-infrared remote sensing and spectral imaging devices, in particular the development of quantum-dot infrared photodetectors [ 58 , 59 ]. As in the number of cases already considered by us, it should be emphasized that the knowledge of bandstructure here is critical too, because, e.g., the bias-dependent spectral response of these devices is brought about by the asymmetric bandstructure of the dot-in-a-well configuration.…”
Section: Low-dimensional Nanostructures and Sensorsmentioning
confidence: 99%
“…We have also shown that UC occurs in QWIs most likely by biexciton Auger interaction, and that its efficiency may exceed that of QDs by proper control. This opens novel possibilities for applications such as intermediate band solar cells [52][53][54] or infrared (IR) detectors 55) based on UC.…”
Section: Introductionmentioning
confidence: 99%
“…The use of In(Ga)As/GaAs QDs in microlasers as an active region provides such advantages as high operating temperature, improved temperature stability of characteristics, low threshold current, low sensitivity to nonradiative recombination [9,10]. The use of In(Ga)As/GaAs QDs in detectors helps to reduce the dark current and improve the sensitivity [11][12][13]. An 11 µm × 90 µm waveguide photodetector with InAs QDs heterogeneously integrated on Si exhibits the maximum responsivity of 0.34 A W −1 at 1310 nm and the openeye diagrams up to 12.5 Gb s −1 together with the minimum dark current of 1 µA cm −2 [14].…”
Section: Introductionmentioning
confidence: 99%